2019
DOI: 10.1080/15384101.2019.1669389
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: 1,25(OH)2D3 improves blood lipid metabolism, liver function, and atherosclerosis by constraining the TGF-β/Smad signaling pathway in rats with hyperlipidemia

Abstract: 1,25(OH) 2 D 3 has already been reported to function in some diseases. However, its role in hyperlipidemia (HLP) remains unknown. This study aims to investigate the effect of 1,25(OH) 2 D 3 on HLP rats. Rat models were established by high-fat diet feeding, perfusion of different doses of 1,25-(OH) 2 D 3 and injection of TGF-β1 siRNA. Whole blood viscosity, plasma viscosity, hematocrit, and erythrocyte aggregation index were detected, together with levels of biochemical indexes, 6keto-PGF1α, and TXB2 in serum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The defense system of SOD and GSH-Px antioxidant enzymes is the first line of defense against oxidative injury in mammalian systems 19 , 20 . In this study, exercise was found to increase the SOD and GSH-Px levels, which is consistent with the findings of Lu et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…The defense system of SOD and GSH-Px antioxidant enzymes is the first line of defense against oxidative injury in mammalian systems 19 , 20 . In this study, exercise was found to increase the SOD and GSH-Px levels, which is consistent with the findings of Lu et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…At a vascular level, the principal effect of vitamin D is an antioxidant action, by superoxide dismutase stimulation ( 22 ), counteracting the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, that promotes the synthesis of reactive oxygen species (ROS). As a consequence of its antioxidant action ( 42 , 43 ), vitamin D exerts beneficial effects on endothelial function ( 22 , 44 ), platelet aggregation ( 45 , 46 ), vascular inflammation ( 47 , 48 ), thrombogenesis ( 49 , 50 ), and vascular resistances and remodeling ( 51 53 ). Of note, vitamin D plays also a role in the regulation of angiogenesis and vascular repair by the synthesis of vascular endothelial growth factor (VEGF) and cell-derived factor 1 (SDF-1), respectively ( 54 , 55 ).…”
Section: Vitamin D and Cv Homeostasismentioning
confidence: 99%
“…Additionally, it is important in regulating metabolic functions. 1,25(OH) 2 D 3 is able to improve lipid metabolism by restricting the TGF‐α/Smad signaling pathway, 24 as well as reset zinc homeostasis of cancer cells with testosterone and 9‐cis retinoic acid to control citrate metabolism, causing them to switch from energy‐producing to energy‐preserving phenotypes 25 . Compelling evidence has suggested that 1,25(OH) 2 D 3 directly regulates genes related to glucose metabolism, tricarboxylic acid cycle (TCA), and oxidative phosphorylation (OXPHOS) and induces tolerance of human dendritic cells by activating intracellular metabolic pathways 26 .…”
Section: Introductionmentioning
confidence: 99%